2020
DOI: 10.1002/fsh.10438
|View full text |Cite
|
Sign up to set email alerts
|

Lingering Taxonomic Challenges Hinder Conservation and Management of Global Bonefishes

Abstract: Despite expanding research on the popular recreational fishery, bonefish taxonomy remains murky. The genus Albula, comprising these iconic circumtropical marine sportfishes, has a complex taxonomic history driven by highly conserved morphology. Presently, 12 putative species are spread among 3 species complexes. The cryptic morphology hinders visual identification, requiring genetic species identification in some cases. Unclear nomenclature can have unintended consequences, including exacerbating taxonomic unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 82 publications
1
35
0
Order By: Relevance
“…These differences indicate a period of sexual inactivity over the summer months and a protracted spawning season in the fall and winter.4 | DISCUSSION4.1 | Species distributions and population connectivityThis study provides the first genetic identifications of Albula spp. from the northern Indian Ocean, a vital prerequisite to conservation efforts for this group of fishes in a severely understudied region(Pickett et al, 2020). The authors of this study found A. glossodonta in the Red Sea and A. oligolepis in the Gulf of Aden, consistent with morphological records from each respective location(GBIF, 2020;Hidaka et al, 2008).…”
supporting
confidence: 82%
See 4 more Smart Citations
“…These differences indicate a period of sexual inactivity over the summer months and a protracted spawning season in the fall and winter.4 | DISCUSSION4.1 | Species distributions and population connectivityThis study provides the first genetic identifications of Albula spp. from the northern Indian Ocean, a vital prerequisite to conservation efforts for this group of fishes in a severely understudied region(Pickett et al, 2020). The authors of this study found A. glossodonta in the Red Sea and A. oligolepis in the Gulf of Aden, consistent with morphological records from each respective location(GBIF, 2020;Hidaka et al, 2008).…”
supporting
confidence: 82%
“…The results provide support for the continued, widespread use of Forsskål's original A. glossodonta description (Red Sea, Jeddah, Saudi Arabia; Forsskål, 1775) and provide evidence against direct suggestions from published literature that an undescribed Albula lineage may occur in the Red Sea (Colborn et al, 2001). The presence of A. glossodonta in the Red Sea is not surprising as the species exhibits a relatively long pelagic larval duration (c. 57 days) and is the most widely distributed species within its genus (Colborn et al, 2001;Friedlander et al, 2008;Pickett et al, 2020;Wallace, 2015 Gaither et al, 2011).The F st analyses in this study, driven by unique haplotypes, reflected high differentiation between basins.…”
Section: Growthmentioning
confidence: 93%
See 3 more Smart Citations